Visual prosody supports reading aloud expressively - Bessemans, Ann; Renckens, Maarten; Bormans, Kevin; Nuyts, Erik; Larson, Kevin (Visible Language, 2019)
Type is not expressive enough. Even the youngest speakers are able to express a full range of emotions with their voice, while young readers read aloud monotonically as if to convey robotic boredom. We augmented type to convey expression similarly to our voices. Specifically, we wanted to convey in text words that are spoken louder, words that drawn out and spoken longer, and words that are spoken at a higher pitch. We then asked children to read sentences with these new kinds of type to see if children would read these with greater expression. We found that children would ignore the augmentation if they weren’t explicitly told about it. But when children were told about the augmentation, they were able to read aloud with greater vocal inflection. This innovation holds great promise for helping both children and adults to read aloud with greater expression and fluency.